If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 = 3x + 18 Reorder the terms: 27 = 18 + 3x Solving 27 = 18 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 27 + -3x = 18 + 3x + -3x Combine like terms: 3x + -3x = 0 27 + -3x = 18 + 0 27 + -3x = 18 Add '-27' to each side of the equation. 27 + -27 + -3x = 18 + -27 Combine like terms: 27 + -27 = 0 0 + -3x = 18 + -27 -3x = 18 + -27 Combine like terms: 18 + -27 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| (4+6i)+(2+6i)= | | 3e^7x=1056 | | 2w=-7/5 | | (M-4/3)-(3m-1/5)=1 | | 3-2i=-12x+4yi | | 4(n+8)+n=6(n-4)+3n | | 4=4x-20 | | 1-4v-2=-25-6r | | (8x+6)(6x^2+6x+6)=0 | | (5-3i)/(6-4i) | | 16x^2+12X^2= | | x^2+8x-3.5=0 | | 5x-(2x+3)=4x-29 | | 2/3w=-4/9 | | x+3=5.6 | | 12y+21=9y+27 | | (5x+8y)(7x-2y)= | | 2-x=-2x-10 | | 8m-(3/4)=(11/12) | | 20+.2x=x | | -4/7=y/21 | | -5+3x=5x-12 | | 8x-(9x+3)=6x-10 | | ln(3x-17)=6 | | 6.2+6.5+3.7=0 | | x+(-25)=-30 | | 3x+2x=45-3x | | 9(x-7)=-513 | | a-72=-18 | | 2+4v=38 | | 2x+5y-3x-4y= | | 3x+0.7=9.7 |